2010
DOI: 10.1590/s1413-82712010000100005
|View full text |Cite
|
Sign up to set email alerts
|

Equivalência semântica da versão em português da Escala de Experiência de Quase-Morte

Abstract: ResumoNa literatura internacional, a experiência de quase-morte (EQM) é avaliada principalmente por meio do instrumento The Near-Death Experience Scale (NDE), elaborado por Bruce Greyson, em 1983. O objetivo do presente estudo é verificar a existência de equivalência semântica entre a versão original da escala (em inglês) e a versão traduzida ao português do Brasil, avaliando os significados geral e referencial. Após as diversas etapas de avaliação da equivalência semântica, a escala foi pré-testada em seis pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
3
0
3
Order By: Relevance
“…At the evaluation stage of semantic equivalence, the concern is about understanding the procedure to all the intended population members (25) . It is observed that choosing different expert translators for the procedure thematic to be adapted for Brazil, has been a concern of the researchers (26) .…”
Section: Discussionmentioning
confidence: 99%
“…At the evaluation stage of semantic equivalence, the concern is about understanding the procedure to all the intended population members (25) . It is observed that choosing different expert translators for the procedure thematic to be adapted for Brazil, has been a concern of the researchers (26) .…”
Section: Discussionmentioning
confidence: 99%
“…For certification that the instrument is understandable to all members of the population for which it is intended (27) , you must perform the cross-cultural adaptation, emphasizing the semantic equivalence of the terms and not in the literal equivalence. Translation step of a procedure requires linguistic care, because terms may have different meanings and specificities inherent to each language (27) .…”
Section: Discussionmentioning
confidence: 99%
“…Translation step of a procedure requires linguistic care, because terms may have different meanings and specificities inherent to each language (27) . Therefore, the use of four translators was extremely useful for the construction of the Portuguese version of DASH, since all versions could be confronted and discussed with the committee of experts.…”
Section: Discussionmentioning
confidence: 99%
“…O sofrimento psicológico subsequente à exposição a um evento traumático ou estressante pode estar presente após a EQM, por esta ser considerada uma vivência atípica, causadora de forte impacto emocional (SERRALTA et al, 2010). Esse sofrimento pode causar reações subjetivas como medo, hipervigilância, insegurança, sentimentos de raiva, alterações no funcionamento cognitivo, afetivo e também objetivas, como alterações comportamentais (KNAPP, 2009).…”
Section: Pela Eqmunclassified